Evaluation of the effects of a drug with fiscalized substance dispensation, health education, and pharmacovigilance continuing education program in Colombia drugstores and drugstores/pharmacies: study protocol of a multicenter, cluster-randomized controlled trial (2020)
ABSTRACT: Background: Health disorders, due to the use of drugs with fiscalized substances, including controlled substances, have become a common problem in Colombia. Multiple reasons can help explain this problem, including selfmedication, since access to these drugs may be easier. Also, there is a lack of knowledge that these drugs are safer than illicit drugs. The use of these drugs without a valid medical prescription and follow-up can have negative consequences such as drug abuse, addiction, and overdose, and eventually, have negative health consequences. Pharmacy staff is essential to both assure the correct drug use and minimize prescription errors to help outpatients have better management of their pharmacotherapy. For this reason, it is necessary to increase key competencies like knowledge, skills, and attitudes in the pharmacy staff of ambulatory (outpatients) pharmacies. Methods: This study is a prospective, cluster-randomized, parallel-group, multicenter trial of drugstores and drugstores/pharmacies (ambulatory pharmacies). The study is designed to determine the effectiveness of a drug with fiscalized substance dispensation, health education, and pharmacovigilance continuing education program in drugstores and drugstores/pharmacies. Pharmacy staff will be randomly selected and assigned to one of the study groups (intervention or control). The intervention group will receive a continuing education program for over 12 months. The control group will receive only general information about the correct use of complex dosage forms. The primary objective is to evaluate the effectiveness of a continuing education program to improve pharmacy staff competencies (knowledge, skills, and attitudes) to improve the ambulatory (outpatient) pharmacy services: dispensation, health education, and pharmacovigilance of drugs with fiscalized substances. The secondary outcomes include (a) processes associated with the management of drugs with fiscalized substances in drugstores and drugstores/pharmacies, including regulation compliance; (b) degree of implementation of ambulatory (outpatient) pharmacy services targeting these drugs in drugstores and drugstores/pharmacies; (c) patient satisfaction with such services; and (d) pharmacy staff satisfaction with the continuing education program. Discussion: This clinical trial will establish whether providing a continuing education program for the adequate utilization of drugs with fiscalized substances improves pharmacy staff competencies regarding these drugs. Trial registration: ClinicalTrials.gov NCT03388567. Registered on 28 November 2017. First drugstore or drugstore/pharmacy randomized on December 1, 2018. Protocol version: 0017102017MC